2021
DOI: 10.1016/j.anai.2020.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Factors contributing to underuse of epinephrine autoinjectors in pediatric patients with food allergy

Abstract: Background: Epinephrine autoinjectors (EAs) are the standard of care for severe food allergic reactions, although they are frequently underused or misused. Objective: To understand the factors associated with underuse of EA by caregivers of pediatric patients with food allergy. Methods: A survey was administered to 200 caregivers of pediatric patients with food allergies to assess most severe lifetime allergic reaction, EA education, and use and factors associated with incorrect use or underutilization. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 22 publications
0
29
0
Order By: Relevance
“…Results are in line with previous researches ( 11 19 ) and support the importance of investigating the reasons why parents do not act properly in case of anaphylaxis. A recent study involving 164 caregivers ( 17 ) reported that the majority did not give their allergic children AAI at the time of their most severe allergic reactions, despite declaring confidence in their ability to treat allergic reactions. Reasons caregivers indicated for not administering the AAI included the following: reactions did not seem severe enough; use of other medication; and fear of using AAI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Results are in line with previous researches ( 11 19 ) and support the importance of investigating the reasons why parents do not act properly in case of anaphylaxis. A recent study involving 164 caregivers ( 17 ) reported that the majority did not give their allergic children AAI at the time of their most severe allergic reactions, despite declaring confidence in their ability to treat allergic reactions. Reasons caregivers indicated for not administering the AAI included the following: reactions did not seem severe enough; use of other medication; and fear of using AAI.…”
Section: Discussionmentioning
confidence: 99%
“…A study involving 165 parents reported that parental empowerment directly correlated with increased comfort with AAI use, but knowledge did not ( 16 ). Other researches ( 3 , 11 , 17 ) found that the most common reasons among parents for not using adrenaline despite carrying was concern about adverse effects, fear about the injection, and not wanting to activate emergency services or go to the emergency department.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…New pharmacological therapies in the management of food allergies aim at regulating inducing cells and suppressing the native and adaptive responses responsible for triggering allergic reactions [65][66][67]. These therapies are not allergen-dependent, acting nonspecifically, which differentiates them from immunotherapy.…”
Section: Pharmacological Treatmentmentioning
confidence: 99%
“…Recent publications identify this barrier to epinephrine use, citing avoidance of the ED during the COVID-19 pandemic as a factor in up to 20% of anaphylaxis cases in which epinephrine is not used. 8,9 This effect is likely to be observed during cases in which anaphylaxis symptoms are mild or subjective and when caregivers are inexperienced in recognizing symptoms or fearful of epinephrine self-administration. In addition, such an effect may be disparately observed among those patients already burdened by certain socioeconomic determinants of health, including financial strain, possibly widening health care disparities.…”
mentioning
confidence: 99%